Content Analysis of the Construction of Self and Others in Women with Bulimia Nervosa - Dada, Gloria; Izu, Sheila; Montebruno, Claudia; Grau, Antoni; Feixas, Guillem (Frontiers in Psychology, 2017)
The purpose of this study is to explore the content of personal constructs in people diagnosed with bulimia nervosa (BN). We expect to find differences in the predominant content of the construct systems between women with and without BN. We analyzed the constructs elicited using the repertory grid technique from 120 women aged between 18 and 45 years, divided into two groups: a clinical group of women diagnosed with bulimia (n = 62) and a control group of university students without disorder (n = 58). The constructs were categorized using the Classification System for Personal Constructs (CSPC), composed of six thematic which are broken down into 45 categories. For this study, a new area called "Physical" is included, and it consists of three categories. The results indicated that women diagnosed with bulimia used significantly more constructs related to the body, while the control group used more constructs from the personal area. In addition, the congruent constructs from the clinical sample were predominantly moral, or related to values and interests, while discrepant constructs were personal and physical. The findings provide evidence for the clinical use of the CSPC as an instrument for exploring the content of personal meaning systems. Understanding the patient’s constructions about herself, others, in her own way of construing is useful for treatment. Moreover, it is important for clinicians to explore the content of constructs related to symptomatic areas, that could be hindering change, and focus on them to facilitate improvement.